2′,3′,4′-Trihydroxychalcone changes estrogen receptor α regulation of genes and breast cancer cell proliferation by a reprogramming mechanism - Candice B. Herber; Chaoshen Yuan; Anthony Chang; Jen-Chywan Wang; Isaac Cohen; Dale C. Leitman (Molecular Medicine, 2022)
Abstract Background Menopausal hormone therapy (MHT) is recommended for only five years to treat vasomotor symptoms and vulvovaginal atrophy because of safety concerns with long-term treatment. We investigated the ability of 2′,3′,4′-trihydroxychalcone (2′,3′,4′-THC) to modulate estrogen receptor (ER)-mediated responses in order to find drug candidates that could potentially prevent the adverse effects of long-term MHT treatment. Methods Transfection assays, real time-polymerase chain reaction, and microarrays were used to evaluate the effects of 2′,3′,4′-THC on gene regulation. Radioligand binding studies were used to determine if 2′,3′,4′-THC binds to ERα. Cell proliferation was examined in MCF-7 breast cancer cells by using growth curves and flow cytometry. Western blots were used to determine if 2′,3′,4′-THC alters the E2 activation of the MAPK pathway and degradation of ERα. Chromatin immunoprecipitation was used to measure ERα binding to genes. Results The 2′,3′,4′-THC/E2 combination produced a synergistic activation with ERα on reporter and endogenous genes in human U2OS osteosarcoma cells. Microarrays identified 824 genes that we termed reprogrammed genes because they were not regulated in U2OS-ERα cells unless they were treated with 2′,3′,4′-THC and E2 at the same time. 2′,3′,4′-THC blocked the proliferation of MCF-7 cells by preventing the E2-induced activation of MAPK and c-MYC transcription. The antiproliferative mechanism of 2′,3′,4′-THC differs from selective estrogen receptor modulators (SERMs) because 2′,3′,4′-THC did not bind to the E2 binding site in ERα like SERMs. Conclusion Our study suggests that 2′,3′,4′-THC may represent a new class of ERα modulators that do not act as a direct agonists or antagonists. We consider 2′,3′,4′-THC to be a reprogramming compound, since it alters the activity of ERα on gene regulation and cell proliferation without competing with E2 for binding to ERα. The addition of a reprogramming drug to estrogens in MHT may offer a new strategy to overcome the adverse proliferative effects of estrogen in MHT by reprogramming ERα as opposed to an antagonist mechanism that involves blocking the binding of estrogen to ERα.